Coram House : a novel - Seybolt, Bailey (Atria Books, 2025)
"In this debut that's perfect for fans of Tana French and Gillian Flynn, a true crime writer risks becoming the next chapter of a crumbling orphanage's dark legacy as she unravels the mystery of two deaths, decades apart"--